Development of a Disease Modeling Framework for Glutamatergic Neurons Derived from Neuroblastoma Cells in 3D Microarrays - Nguyen, Duc Long; Le, My Phuong Thi; Lee, Kyung Won; Kim, Jae Ho; Yoon, Hyun C.; Pham, Huyen T.M. (Scientific Reports, 2024)
Neurodegenerative diseases (NDDs) present significant challenges due to limited treatment options, ethical concerns surrounding traditional animal models, and the time-consuming and costly process of using human-induced pluripotent stem cells (iPSCs). We addressed these issues by developing a 3D culture protocol for differentiating SH-SY5Y cells into glutamatergic neurons, enhancing physiological relevance with a 3D microarray culture plate. Our protocol optimized serum concentration and incorporated retinoic acid (RA) to improve differentiation. We analyzed the proportions of N-type and S-type cells, observing that RA in the maturation stage not only reduced cell proliferation but also enhanced the expression of MAP2 and VGLUT1, indicating effective neuronal differentiation. Our approach demonstrates the strong expression of glutamatergic neuron phenotypes in 3D SH-SY5Y neural spheroids, offering a promising tool for high-throughput NDD modeling and advancing drug discovery and therapeutic development. This method overcomes limitations associated with conventional 2D cultures and animal models, providing a more effective platform for NDD research.
Keywords: Cell Culture Techniques; Cell Culture Techniques, Three Dimensional; Cell Differentiation; Cell Line, Tumor; Cell Proliferation; Glutamic Acid; Humans; Induced Pluripotent Stem Cells; Neuroblastoma; Neurodegenerative Diseases; Neurons; Spheroids, Cellular; Tretinoin; 3D microarrays; Disease modeling; Glutamatergic neuron; Retinoic acid; SH-SY5Y cells